GdPtBi Heuslerene: mechanical stability, half-metallic, magneto-optic, and thermoelectric properties by DFT. Issue 10 (19th May 2022) - Hosseinzadeh, Farnaz; Boochani, Arash; Elahi, Seyed Mohammad; Ghorannevis, Zohreh
ABSTRACT: Based on Density Functional Theory (DFT) calculations, the mechanical stability from a static and dynamic point of view and the electronic, magneto-optic, and thermoelectric properties GdPtBi Heuslerene have been investigated. This compound has a ground state point, and its phonon branches in the Brillouin zone are all positive, which indicates its mechanical stability. Based on the HSE approximation, this compound shows a Half-metallic behaviour with 100% spin polarisation. In addition, the Magneto Optic Kerr Effect (MOKE) property indicates that the θK angle is equal to two at the UV edge, which refers to considerable magneto-optical polarisation. Also, the Seebeck and power factor coefficients have peaks at room temperature.